Free Vibration Analysis for Polyester/Graphene Nanocomposites Multilayer Functionally Graded Plates - Abd Alqader, Shahad Qusi; Bedaiwi, Bashar Owaid; Njim, Emad Kadum; Takhakh, Ayad M.; Hadji, Lazreg (Physics and Chemistry of Solid State, 2024)
In the current work, an FGM nanocomposite made of multi-layers of graphene nanoparticles and a polyester-based matrix was constructed using the molds with a hand lay-up technique to attain an accurate shape and reduce defects in the final product. The desired models have four, six, and 11 layers and different volume fractions of nanoparticles (0.5, 1, 2, 3, 4, and 5%). This study conducted various experimental tests to analyze the free vibration characteristics of functionally graded composite sandwich rectangular structures with simply supported boundary conditions to evaluate the significance of hole number and cutout location in fundamental frequencies. For holes, three types are used (2, 4, and 6) holes with a 10 mm diameter, while for cutouts, three geometrical designs are used (circular, rectangular, and triangular) with various aspect ratios (r = 1, 1.5, 2, and 2.5). A numerical study was carried out to validate the experimental solution, employing modal analysis and finite element analysis (FEA) using ABAQUS software tools. From the findings, the experimental findings and numerical calculations exhibit a satisfactory level of concurrence, displaying a maximum discrepancy of 9.5%. The results show that the fundamental frequency decreases by increasing the cutouts' aspect ratio (r=a/b). There is minimal variation between r =1 and r= 1.5, but a noticeable decrease is observed at an aspect ratio of r= 2.5. This difference is primarily influenced by the type of material gradient and the number of holes, specifically for a given thickness of the functionally graded (FG) plates.